Pengembangan Potensi Wisata Car Free Day Untuk Pemberdayaan Ekonomi Masyarakat Di Desa Kertaraharja, Kabupaten Ciamis - Ricky Hermayanto; Lati Sari Dewi; Siti Amirah Makarim; Iwan Sugianto; Iwan Saputra; Mohammad Nazirwan (CV. SINAR HOWUHOWU, 2026)
This community service program aims to empower the community in Kertaraharja Village, Ciamis Regency, through the development of its Car Free Day (CFD) tourism potential. Kertaraharja Village boasts beautiful natural landscapes, including vast rice fields and views of Mount Sawal, which are utilized as a Car Free Day location every Sunday. This CFD event not only serves as a culinary and sports tourism destination but also provides a platform for numerous Micro, Small, and Medium Enterprises (MSMEs) to sell their products. However, optimizing this potential still faces challenges related to marketing, product diversification, and community participation. The methods used in this activity include identifying tourism potential, conducting a SWOT analysis to formulate development strategies, and implementing digital marketing and MSME empowerment programs. The activity was carried out with a participatory approach through training and mentoring for local communities and MSME actors. The results indicate that Kertaraharja Village has significant potential for developing sustainable tourism through CFD, but requires continuous management and innovative marketing strategies. The community empowerment strategies implemented include strengthening MSME institutions, diversifying culinary and local products, and utilizing digital platforms for promotion. This approach has been proven to increase local economic activity, product diversification, and strengthen community institutions, thereby contributing to improving the economic welfare of the community in a sustainable manner.